Procurement Planning and Performance of Public Hospitals in Kisii County - Nyabuto, Alex Mageria; Juma, Dennis (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study sought to examine the effect of key procurement planning components on hospital performance. The specific objectives were: (i) to examine the relationship between needs assessment and hospital performance, (ii) to determine the influence of supplier selection on hospital performance, (iii) to assess the impact of budgeting practices on hospital performance, and (iv) to evaluate the role of ICT integration in enhancing procurement performance. Methodology: A descriptive research design was adopted. The target population comprised 70 procurement, finance, and management personnel from selected public hospitals in Kisii County. A census sampling technique was used due to the manageable size of the population. Primary data were collected using a structured Likert-scale questionnaire, and the data were analyzed using both descriptive and inferential statistics. Findings: Findings indicated that all four independent variables needs assessment, supplier selection, budgeting practices, and ICT integration positively and significantly influenced the performance of public hospitals. Specifically, needs assessment was found to enhance efficiency in resource utilization; supplier selection improved reliability and service quality; budgeting practices supported financial discipline; and ICT integration streamlined operations and reduced delays. Unique Contribution to Theory, Policy and Practice: The study recommends institutionalizing data-driven needs assessment, enforcing transparent and criteria-based supplier selection, improving budget coordination between procurement and finance units, and investing in modern ICT systems and staff training. These findings offer actionable insights for policymakers, hospital administrators, and procurement professionals aiming to improve the efficiency and effectiveness of public healthcare delivery.